Building safer cars. - Jones, W.D (IEEE spectrum)
In the future, cars will help make the world's roads nearly accident free. Humans are fallible: we get sleepy while driving at night, do dumb things like put on makeup or shave while creeping along in bumper-to-bumper traffic, or look away from the road to adjust our car radios. But cars will soon make road travel safer by looking over drivers' shoulders, so to speak, keeping their attention from being pulled away from the road, and finding ways to reduce the hazard should a driver's focus stray. To this end, researchers envision smart systems that give the driver "the right information, in the right way, at the right time". R&D programs are advancing toward a smart car capable of reducing the number of stimuli, some of them simultaneous, to which a driver must react, or taking over elements of the driving task such as braking or steering. Adaptive cruise control (ACC) systems are being developed which combine radar- or laser-based sensors that scan the road ahead with throttle and brake actuators, to maintain a safe, preset minimum distance between cars in the same lane